Itu Analisis SWOT: Strategi Pemasaran untuk Meningkatkan Penjualan - Larasati, Mayang; Albar, Berri Brilliant; Sari, Junia Mayang (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2025)
This research aims to identify effective marketing strategies to increase sales. Thus, leads to business existence and sustainability. This research is classified as field research with a descriptive qualitative approach and has selected 14 food vendors at Pantai Padang as a sample group using nonprobability sampling, namely snowball sampling. Previous research explores strategies to increase sales for various businesses, but there is a dearth of research focusing on marketing strategies tailored to traders operating within a specific environment. To address this gap, a SWOT analysis was conducted to assess the strengths, weaknesses, opportunities, and threats facing the merchants. This study uses IFAS (Internal Factor Analysis Summary) and EFAS (External Factor Analysis Summary) to assess the internal and external factors that influence the sustainability and performance of their businesses. The results of the IFAS analysis showed strong internal environmental conditions. The EFAS analysis shows that the traders are effectively capitalizing on opportunities while mitigating threats. In the Cartesian diagram, the SWOT analysis is in the first quadrant, known as the aggressive strategy quadrant, which is favorable for the business. The analysis performed will influence the long-term viability of the business, encompassing continuous operations, growth, strategic development to ensure business continuity, and expansion efforts, all of which contribute to the sustainability and ongoing existence of the business. Keywords: Marketing Strategy; MSMEs; SWOT; IFAS; EFAS